Wild-Type α-Synuclein and Variants Occur in Different Disordered Dimers and Pre-Fibrillar Conformations in Early Stage of Aggregation - Guzzo , Adrien; Delarue , Patrice; Rojas, Ana; Nicolaï , Adrien; Maisuradze , Gia G.; Senet, Patrick (Frontiers in Molecular Biosciences, 2022)
alpha-synuclein is a 140 amino-acid intrinsically disordered protein mainly found in the brain. Toxic alpha-synuclein aggregates are the molecular hallmarks of the Parkinson disease. In vitro studies showed that alpha-synuclein aggregates in oligomeric structures of several tenth of monomers and into cylindrical structures (fibrils), comprising hundred to thousands proteins, with polymorphic cross-beta-sheet conformations. Oligomeric species, formed at the early stage of aggregation remain, however, poorly understood and are hypothezised to be the most toxic aggregates. Here, we studied the formation of wild-type (WT) and mutants (A30P, A53T, and E46K) dimers of alpha-synuclein using coarse-grained molecular dynamics. We identified two principal segments of the sequence with an higher propensity to aggregate in the early stage of dimerization: residues 36-55 and residues 66-95. The transient alpha-helices (residues 53-65 and 73-82) of alpha-synuclein monomers are destabilized by A53T and E46K mutations which favors the formation of fibril native contacts in the N-terminal region, whereas the helix 53-65 prevents the propagation of fibril native contacts along the sequence for the WT in the early stages of dimerization. The present results indicate that dimers do not adopt the Greek-key motif of the monomer fold in fibrils but form a majority of disordered aggregates and a minority (9-15 %) of pre-fibrillar dimers both with intra-molecular and inter-molecular beta-sheets. The percentage of residues in parallel beta-sheets is by increasing order monomer < disordered dimers < pre-fibrillar dimers. Native fibril contacts between the two monomers are present in the NAC domain for WT, A30P and A53T and in the N-domain for A53T and E46K. Structural properties of pre-fibrillar dimers agree with rupture-force Atomic Force Microscopy and single-molecule Förster Resonance Energy Transfer available data. This suggests that the pre-fibrillar dimers might correspond to the smallest type B toxic oligomers. The probability density of the dimer gyration radius is multi-peaks with an average radius which is 10 angstroems larger than the one of the monomers for all proteins. Taken all together these results indicate that even the elementary alpha-synuclein aggregation step, the dimerization, is a complicated phenomena which does not only involved the NAC region.